Evaluasi Program PKL Kompetensi Keahlian Teknik Kendaraan Ringan di SMK Negeri 39 Jakarta - Hafizh Taufiqurahman dan Musringudin (JOURNAL SCIENTIFIC OF MANDALIKA (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2022)
This study aims to describe what it is about the application of e-learning in the Educational Technology Study Program of the Faculty of Education and Psychology at Mandalika University of Education. This research uses a case study method with various data collection techniques. The results showed that: 1) there were 20 courses held by e-learning by 7 lecturers; 2) e-learning applied is blended learning; 3) the application of e-learning has gone through the stages of analysis, design and development; 4) the analysis phase includes the analysis of student characteristics and e-learning environment analysis); 5) the design phase where most are designed with online learning patterns (studying the material, deepening the material through online discussion forums, applying knowledge through online assignments, and evaluating through online tests and face-to-face learning more emphasis on in-depth discussion, demonstrations, case studies, and practice; 6) the development phase of lecturers developing material by utilizing existing material; 7) the implementation of blended learning is interesting and liked by students; 8) the implementation of e-learning is going well because of the strong commitment of the lecturers, the familiarity of students' ICT and study program support; and 9) the inhibiting factors for the adoption of e-learning are more on the lack of inadequate ICT policy and infrastructure support. Based on research findings it is recommended that educational technology study programs have a minimum standard of developing and implementing blended learning and increasing the support of adequate facilities and access to the internet.